Silicon-graphene composite negative electrode material and preparation method thereof
The improved Hummers method is used to prepare graphene oxide and reduced graphene oxide powder, combined with commercial carbon sources and silicon metal particles, and spray drying and heat treatment processes are used to prepare silicon-graphene composite negative electrode materials, which solves the problem of excessive volume expansion of silicon negative electrode materials during charging and discharging, and achieves the dual advantages of the stability of secondary batteries and high storage capacity.
Patent Information
- Application Number
- CN202380062105.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-02
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-18
AI Technical Summary
The volume expansion of the silicon negative electrode material during charging and discharging is too large, resulting in micronization and excessive generation of solid film (SEI), affecting the stability of the secondary battery and the performance of high storage capacity.
The aqueous graphene oxide solution was prepared by the improved Hummers method, and reduced graphene oxide powder was prepared by drying and reducing. Combined with commercial carbon sources, polymers and silicon metal particles, the silicon-graphene composite negative electrode material was prepared by spray drying and heat treatment to form a core-shell structure to inhibit volume expansion.
It effectively suppresses the volume expansion of the negative electrode material during charging and discharging, reduces the micronization of silicon and the generation of solid film (SEI), improves the stability of the secondary battery, and maintains the inherent high storage capacity of silicon.
Smart Images

Figure CN119856293A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon-graphene composite negative electrode material and a preparation method thereof, and more specifically, to a silicon-graphene composite negative electrode material comprising a graphene oxide aqueous solution prepared by an improved Hummers method and a reduced graphene oxide powder prepared by drying and reducing the graphene oxide aqueous solution, a commercial carbon source, a polymer including salts and silicates, a water-soluble polymer and silicon metal particles, and prepared by a process of spray drying and heat treatment. The silicon-graphene composite negative electrode material has the advantages of suppressing the high volume expansion of the negative electrode material during charging and discharging, the micronization of silicon caused thereby and the excessive generation of a solid film (Solid Electrolyte Interphase, SEI) on the surface of the negative electrode material, so that a secondary battery based on the silicon negative electrode material can work stably, and at the same time can exhibit the advantages of high storage capacity inherent in silicon, and a preparation method thereof. Background Art
[0002] Graphene is a two-dimensional nanostructure composed of a layer of carbon. It is a substance in the form of a single flat hexagonal lattice formed by sp2 hybrid bonding of carbon atoms. The graphene is the same as the hexagonal lattice in that the graphite with a layered structure is completely separated from the interlayer. Graphene was first made by the University of Manchester in the UK using the "scotch tape method" in 2004. After that, Columbia University in the United States confirmed the excellent strength of graphene in 2008. In the same year, Columbia University in the United States confirmed that the thermal conductivity of graphene is 5300W / mK, which is twice that of carbon nanotubes. If the carbon nanotube is cut in the length direction, it becomes a graphene structure. If the wall diameter of the carbon nanotube is infinitely expanded, it becomes similar to the graphene structure. Therefore, the electrical, thermal and mechanical properties of graphene are comparable to those of carbon nanotubes. On the other hand, compared with carbon nanographene, graphene has a plate-like structure, which is different from carbon nanotubes with needle-like structures. Therefore, graphene also has the following advantages: it can be made rich in edges to facilitate functionalization according to the intended purpose, and the active surface area is larger, which can be used for shielding and other purposes. In addition, graphene is the thinnest material among existing materials, has a higher current density than copper, and exhibits the characteristics of quantum Hall effect at room temperature that can only be observed at extremely low temperatures. It is the material with the best strength, thermal conductivity, electron mobility and other characteristics among existing materials. It is recognized as a strategic core material that will be used in various fields such as displays, secondary batteries, solar cells, polymer composite materials, composites, coatings, heat dissipation, etc. to promote the growth of related industries.
[0003] On the other hand, with regard to secondary batteries, the world is paying more and more attention to new energy sources as the demand for various miniaturized and lightweight electronic devices and ultra-large power storage systems has increased dramatically recently. Among them, research and development in the field of secondary batteries that are environmentally friendly, have high energy density and can be charged and discharged quickly is being carried out intensively. In particular, carbon-based, metal-based, and oxide-based materials used as negative electrode active materials for lithium secondary batteries are not only diverse, but also play a core role in improving high-power and high-density energy power, so a lot of research and commercialization are being carried out. Among the carbon-based materials mentioned as negative electrode active materials, graphite is a very excellent material that is very stable and does not expand in volume, but due to the limitation of theoretical capacity, it is not enough to be used as a negative electrode active material for mobile devices that require high capacity. Therefore, new high-capacity materials are needed as negative electrode active materials, among which silicon (Si) has a higher theoretical capacity. Silicon is a metallic element that can realize the charging and discharging of lithium ions by alloying with lithium (Li) and alloying (dealloying). Compared with the existing negative electrode active material graphite, it has superior characteristics in terms of capacity per unit weight and capacity per unit volume. Therefore, it is being actively studied as a new generation of high-capacity lithium secondary battery material.
[0004] Korean Patent No. 10-1399042 relates to negative electrode active materials for improving the energy density and life of lithium secondary batteries that require high power and high voltage, and discloses a high-capacity negative electrode material and its preparation technology for improving the energy storage characteristics and life of medium and large lithium secondary batteries. In addition, Korean Patent No. 10-2405622 discloses a silicon-graphene-carbon nanotube core-shell powder with graphene and carbon nanotubes coated on the surface of silicon modified with an alkoxysilane surface modifier and a silicon-graphene-carbon nanotube core-shell composite secondary battery negative electrode material and its preparation method. At the same time, Korean Patent No. 10-2241526 discloses a method for preparing a negative electrode material, wherein the negative electrode material is a negative electrode material comprising a low-defect / high-purity graphene oxide reduction and silicon metal particles. In order to maximize the characteristics of the composite, a negative electrode material slurry prepared by mixing natural graphite and artificial graphite of different sizes and shapes is coated on a current collector to maximize the packing density. A method for preparing a high-density negative electrode material comprising a graphene oxide reduction-silicon metal particle composite containing the negative electrode material prepared by the above method, which can improve the high capacity and stable cycle performance of an electrode for a secondary battery, and an electrode for a secondary battery containing the negative electrode material prepared thereby are also disclosed.
[0005] As mentioned above, there are a variety of negative electrode material preparation technologies using silicon-graphene, but although silicon exhibits high theoretical capacity characteristics, it is difficult to commercialize because when absorbing and storing lithium ions, a large volume expansion of more than 300% occurs due to changes in the crystal structure. In addition, due to the phenomenon of continuous volume changes causing the disintegration of the silicon structure, the initial efficiency and cycle characteristics are reduced, so there are problems such as having to include a technology for improving the reversibility of lithium secondary batteries and maintaining high capacity, so it is necessary to develop graphene-silicon negative electrode materials that can solve these problems. Summary of the invention
[0006] Technical issues
[0007] The present invention is made to solve the above-mentioned problems and to provide necessary techniques.
[0008] The object of the present invention is to provide a silicon-graphene composite negative electrode material and a preparation method thereof. The silicon-graphene composite negative electrode material comprises a graphene oxide aqueous solution prepared by an improved Hummers method and a reduced graphene oxide powder prepared by drying and reducing the graphene oxide aqueous solution, a commercial carbon source, a polymer including salts and silicates, a water-soluble polymer and silicon metal particles. The silicon-graphene composite negative electrode material is prepared by a process of spray drying and then heat treatment. The material has the advantages of suppressing the high volume expansion of the negative electrode material during charging and discharging, the resulting micronization of silicon and the excessive generation of a solid film (Solid Electrolyte Interphase, SEI) on the surface of the negative electrode material, so that a secondary battery based on the silicon negative electrode material can operate stably and exhibit the advantages of high storage capacity inherent in silicon.
[0009] Technical Solution
[0010] In order to solve the above technical problems, according to one embodiment of the present disclosure, a method for preparing a silicon-graphene composite negative electrode material is provided, which is characterized by comprising: a graphene oxide preparation step of preparing a graphene oxide aqueous solution by an improved Hummers method; a reduced graphene oxide preparation step of freeze-drying the graphene oxide aqueous solution prepared in the graphene oxide preparation step and then thermally reducing it to prepare reduced graphene oxide powder; a composite dispersed solution preparation step of adding silicon metal particles, a cross-linking agent and a water-soluble polymer to the graphene oxide aqueous solution prepared in the graphene oxide preparation step and the reduced graphene oxide powder prepared in the reduced graphene oxide preparation step, and then stirring and dispersing them to prepare a composite dispersed solution; and a composite powder preparation step of spray-drying the composite dispersed solution prepared in the composite dispersed solution preparation step to prepare a composite powder in which silicon and graphene form a core-shell structure.
[0011] In the present invention, it is characterized in that in the graphene oxide preparation step, the graphene oxide aqueous solution is prepared by an improved Hummers method, and the improved Hummers method is composed of an oxidation step of preparing a graphite oxide slurry after mixing expanded graphite, potassium permanganate, water and sulfuric acid and maintaining a predetermined temperature to react for a predetermined time, a filtering step of mixing 50 to 200 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry prepared in the oxidation step, and then centrifuging to discharge the filtrate and separate the graphite oxide slurry, and a graphene oxide preparation step of preparing a graphene oxide aqueous solution after mixing 5000 to 20000 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry separated in the filtering step, purifying impurities in an ion resin exchange tower, and filtering.
[0012] Furthermore, it is characterized in that the lateral dimensions of the graphene oxide and the reduced graphene oxide are 1 to 100 μm based on the intermediate particle size D50, and the thickness is 0.6 to 10 nm.
[0013] And, it is characterized in that, in the composite dispersion solution preparation step, the mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is added and dispersed in a ratio of 1 to 3 parts by weight relative to 100 parts by weight of the silicon metal particles.
[0014] Here, it is characterized in that the mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is mixed with the reduced graphene oxide powder in a ratio of not more than 200 parts by weight relative to 100 parts by weight of the graphene oxide aqueous solution.
[0015] And, it is characterized in that the size of the silicon metal particles is 0.05 to 5 μm.
[0016] Furthermore, the size of the silicon metal particles is 0.5 to 1 μm.
[0017] Furthermore, it is characterized in that in the step of preparing the composite dispersed solution, a commercial carbon source consisting of any one or more of natural graphite, artificial graphite, carbon black, acetylene black, graphite intercalated compound (GIC), expanded graphite, activated carbon, graphene nanosheets (GNP) and carbon nanotubes (CNT) is also added and dispersed and mixed.
[0018] Furthermore, it is characterized in that the cross-linking agent is composed of a monomer containing silicate.
[0019] Here, it is characterized in that the monomer containing the silicate is any one of tetraethoxysilane, n-octyltriethoxysilane, siloxane and vinyltrimethoxysilane.
[0020] Furthermore, it is characterized in that silicate is also included in the step of preparing the composite dispersion solution.
[0021] Furthermore, the water-soluble polymer is selected from the group consisting of polyvinyl alcohol, polyethylene glycol, polyethyleneimine, polyamideamine, polyvinylformamide, polyvinyl acetate, polyacrylamide, polyvinylpyrrolidone, polydiallyldimethylammonium chloride, polyethyleneoxide, polyacrylic acid, polystyrenesulfonic acid, polysilicic acid, polyphosphoric acid, polyethylenesulfonic acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylformamide, poly-4-vinyl acetate, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylformamide, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylformamide, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acetate, poly-4-vinyl acid), Polyethylene ohosphoric acid, Polymaleic acid, Poly-4-vinylbenzoic acid, Methyl cellulose, Hydroxy ethyl cellulose, Carboxy methyl cellulose, Sodium carboxy methyl cellulose, Hydroxy propylcellulose, Sodium carboxymethyl cellulose, Polysaccharide, Starch, and any one or more of a mixture thereof.
[0022] Furthermore, it is characterized in that, in the composite powder preparation step, the composite dispersion solution prepared in the composite dispersion solution preparation step is spray-dried at a temperature of 100 to 250°C.
[0023] And, it is characterized in that the size of the composite powder prepared in the composite powder preparation step is 1 to 100 μm.
[0024] Furthermore, it is characterized in that, after the composite powder preparation step, it also includes a heat treatment step of heat treating the composite powder prepared in the composite powder preparation step at a temperature of 100 to 500° C. for 30 minutes to 4 hours in any one of the atmospheric gases selected from air, nitrogen and argon.
[0025] In the present invention, a silicon-graphene composite negative electrode material is provided, characterized in that a core is composed of silicon metal particles and a shell is composed of graphene to form a core-shell structure.
[0026] Another embodiment of the present invention provides a silicon-graphene composite negative electrode material, characterized in that it is prepared by the above method and formed into a core-shell structure.
[0027] Technical Effects
[0028] The silicon-graphene composite negative electrode material prepared according to one embodiment of the present invention comprises a graphene oxide aqueous solution prepared by an improved Hummers method and a reduced graphene oxide powder prepared by drying and reducing the graphene oxide aqueous solution, a commercial carbon source, a polymer including salts and silicates, a water-soluble polymer and silicon metal particles. The silicon-graphene composite negative electrode material is prepared by a process of spray drying followed by heat treatment. The material has the advantages of inhibiting the high volume expansion of the negative electrode material during charging and discharging, the resulting micronization of silicon and the excessive generation of a solid film (Solid Electrolyte Interphase, SEI) on the surface of the negative electrode material, so that secondary batteries based on silicon negative electrode materials can operate stably while exhibiting the advantages of silicon's inherent high storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flow chart showing a method for preparing a silicon-graphene composite negative electrode material according to process steps;
[0030] Figure 2 is a photograph showing the state of a silicon-graphene composite;
[0031] Figure 3 is a graph showing the charge and discharge test results of a silicon-graphene composite negative electrode material;
[0032] Figure 4 It is a graph about the cycle characteristics of silicon-graphene composite negative electrode materials. DETAILED DESCRIPTION
[0033] In a silicon-graphene composite negative electrode material and a preparation method thereof according to one embodiment, a preparation method of a silicon-graphene composite negative electrode material can be provided, characterized in that it includes: a graphene oxide preparation step of preparing a graphene oxide aqueous solution by an improved Hummers method; a reduced graphene oxide preparation step of freeze-drying the graphene oxide aqueous solution prepared in the graphene oxide preparation step and then thermally reducing it to prepare reduced graphene oxide powder; a composite dispersed solution preparation step of adding silicon metal particles, a cross-linking agent and a water-soluble polymer to the graphene oxide aqueous solution prepared in the graphene oxide preparation step and the reduced graphene oxide powder prepared in the reduced graphene oxide preparation step, and then stirring and dispersing to prepare a composite dispersed solution; and a composite powder preparation step of spray-drying the composite dispersed solution prepared in the composite dispersed solution preparation step to prepare a composite powder in which silicon and graphene form a core-shell structure.
[0034] Mode for carrying out the invention
[0035] The following embodiments of the present invention are described in detail so that those skilled in the art can easily implement the present invention. The embodiments of the present invention are provided to more fully describe the present invention to those skilled in the art. Therefore, the embodiments of the present invention can be modified into a variety of other modes, and the scope of the present invention is not limited to the embodiments described below.
[0036] When it is mentioned throughout the specification of the present invention that a part “comprises” a certain constituent element, unless there is a special description to the contrary, it means that other constituent elements may be further included, rather than excluding other constituent elements.
[0037] The terms "about", "substantially", etc. used in the entire specification of the present invention are used as the meaning of the numerical value or close to the numerical value when the inherent preparation and material tolerances are given in the meaning of the description, and are used to prevent malicious infringers from improperly using the disclosure content that mentions accurate numerical values or absolute numerical values to help understand the present invention. The terms "(carrying out) ~" or "step of ~" used in the entire specification of this application do not mean "step for ~".
[0038] The present invention relates to a method for preparing a silicon-graphene composite negative electrode material, comprising the steps of preparing graphene oxide; 100 , reduced graphene oxide preparation step S 200 , Composite Dispersion Solution Preparation Step S 300 And the composite powder preparation step S 400 .
[0039] The following specifically describes a method for preparing a silicon-graphene composite negative electrode material according to one embodiment of the present invention. The silicon-graphene composite negative electrode material (hereinafter, "negative electrode material" or "composite negative electrode material") according to one embodiment of the present invention can be more clearly understood through the following preparation method.
[0040] Figure 1 It is a flow chart showing a method for preparing a silicon-graphene composite negative electrode material according to process steps.
[0041] First, the graphene oxide preparation step (S 100 ).
[0042] According to one embodiment of the present invention, it is characterized in that in the oxidation step S 100 In this study, graphene oxide aqueous solution was prepared by a modified Hummers method.
[0043] According to one embodiment of the present invention, it is characterized in that in the graphene oxide preparation step, a graphene oxide aqueous solution is prepared by an improved Hummers method, and the improved Hummers method consists of an oxidation step of preparing a graphite oxide slurry after mixing expanded graphite, potassium permanganate, water and sulfuric acid and maintaining a predetermined temperature to react for a predetermined time, a filtering step of mixing 50 to 200 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry prepared in the oxidation step, and then centrifuging to discharge the filtrate and separate the graphite oxide slurry, and a graphene oxide preparation step of mixing 5000 to 20000 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry separated in the filtering step, purifying impurities in an ion resin exchange tower, and filtering to prepare a graphene oxide aqueous solution.
[0044] Graphite oxide is easily dispersed in water and exists as a negatively charged thin film in a polar solvent, so an exfoliation process is required to form graphene oxide. The above oxidation step utilizes a chemical exfoliation method called the modified Hummers method. Generally, when graphite itself is exfoliated layer by layer, graphene composed only of sp2 carbon spontaneously aggregates due to electrical and thermodynamic instability. However, according to the present invention, if expanded graphite, potassium permanganate, water and sulfuric acid are mixed and stirred to exfoliate graphite through a strong oxidation reaction, graphene oxide can be stably and easily prepared.
[0045] Therefore, in the graphene oxide preparation step, it is most preferred to prepare the graphene oxide aqueous solution by an improved Hummers method, wherein the improved Hummers method comprises an oxidation step of preparing a graphite oxide slurry by mixing expanded graphite, potassium permanganate, water and sulfuric acid and stirring and maintaining a certain temperature to react for a certain time, a filtering step of mixing 50 to 200 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry prepared in the oxidation step, and then centrifuging to discharge the filtrate and separate the graphite oxide slurry, and a graphene oxide preparation step of preparing a graphene oxide aqueous solution by mixing 5000 to 20000 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry separated in the filtering step, purifying impurities in an ion resin exchange tower, and filtering.
[0046] Afterwards, a reduced graphene oxide preparation step (S 200 ).
[0047] A reduced graphene oxide preparation step may be performed in which the graphene oxide aqueous solution prepared in the graphene oxide preparation step is freeze-dried and then thermally reduced to prepare reduced graphene oxide powder.
[0048] Generally speaking, freeze drying is not suitable when graphene is dispersed using an organic solvent, but in the present invention, by purifying and filtering with water, graphene oxide can be stably dispersed, thereby enabling easy freeze drying.
[0049] Therefore, in the reduced graphene oxide preparation step, it is most preferred to prepare the reduced graphene oxide powder by freeze-drying the graphene oxide aqueous solution prepared in the graphene oxide preparation step and then thermally reducing it.
[0050] Afterwards, the composite dispersion solution preparation step (S 300 ).
[0051] The composite dispersed solution preparation step may be performed by adding silicon metal particles, a crosslinking agent, and a water-soluble polymer to the graphene oxide aqueous solution prepared in the graphene oxide preparation step and the reduced graphene oxide powder prepared in the reduced graphene oxide preparation step, followed by stirring and dispersing to prepare a composite dispersed solution.
[0052] According to one embodiment of the present invention, it is characterized in that the lateral size of the graphene oxide and the reduced graphene oxide is 1 to 100 μm based on the median particle size (D50), and the thickness is 0.6 to 10 nm.
[0053] The reason for limiting the lateral size is to facilitate the formation of graphene-silicon composite powder by wrapping silicon metal particle clusters of about hundreds of nanometers. When the lateral size is smaller than the limited range, silicon cannot be fully wrapped. When the lateral size is larger than the limited range, silicon cannot be wrapped due to the excessive size, making it difficult to form a neat core-shell structure, and the graphene may be folded in a disorderly manner. In addition, when the thickness exceeds 10nm, the number of graphene layers is too large, and it is difficult to expect rigidity close to graphite, which may cause problems such as difficulty in lithium ions penetrating into the interior during charging.
[0054] In addition, it is characterized in that the mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is added and dispersed in a ratio of 1 to 3 parts by weight relative to 100 parts by weight of the silicon metal particles.
[0055] If the weight of graphene is too small, silicon cannot be sufficiently wrapped. If the weight of graphene is too large, silicon is over-wrapped, which may cause a problem of reduced ion conductivity.
[0056] Here, it is characterized in that the mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder contains 200 parts by weight or less of the reduced graphene oxide powder relative to 100 parts by weight of the graphene oxide aqueous solution.
[0057] When the amount of reduced graphene oxide powder added to the mixture is lower than the specified range, the amount of graphene is insufficient to wrap silicon and the conductivity is poor. When the amount added exceeds the specified range, the graphene content is too much, resulting in poor dispersion. Compared with the overall volume of the negative electrode material, the amount of silicon is reduced, so the capacity decreases, and problems such as hindering the smooth migration of lithium ions may occur.
[0058] The reason for using graphene oxide is that it maintains a perfect single-layer sheet morphology in aqueous solution, easily wraps silicon particles or clusters, and improves the dispersibility and utilization of reduced graphene oxide, which has an amorphous morphology that is more wrinkled than a single-layer sheet and has low water dispersibility, so that a uniform and stable quality silicon-graphene composite material can be formed. In addition, the dispersibility of graphene oxide can also act as a dispersant, allowing reduced graphene oxide to form a stable dispersed morphology in water at the same time. The reason why reduced graphene oxide is used together is that it is closer to the morphology of theoretical graphene than graphene oxide, and its electronic conductivity is better than that of graphene oxide.
[0059] In addition, the size of the silicon metal particles is 0.05 to 5 μm. Although not limited thereto, the size of the silicon metal particles is 0.5 to 1 μm.
[0060] When silicon metal particles are smaller than 0.05μm, i.e., the silicon metal particles are too small, a solid film (SEI layer) is formed excessively on the surface of the negative electrode material due to the large surface area during battery manufacturing, which not only reduces the initial efficiency and overall applicability, but also does not need to consider volume expansion and micronization during charging and discharging for small silicon particles of about tens of nanometers. In addition, when silicon metal particles are larger than 1μm, i.e., too large, the rupture phenomenon caused by volume expansion is too serious, so even if they are wrapped with graphene, it will not help, and the problem of reduced charging speed and capacity may occur due to too few effective interfaces.
[0061] According to one embodiment of the present invention, it is characterized in that a commercial carbon source consisting of any one or more of natural graphite, artificial graphite, carbon black, acetylene black, graphite intercalated compound (GIC), expanded graphite, activated carbon, graphene nanosheets (GNP) and carbon nanotubes (CNT) is also added and dispersed and mixed.
[0062] A commercial carbon source is used to consolidate the bonding force of the silicon-graphene mixture and improve the charge conductivity inside the composite powder, and most preferably, a small carbon black with a particle size of about 50 nm is used.
[0063] In addition, the invention is characterized in that the cross-linking agent is composed of a monomer containing silicate.
[0064] Here, it is characterized in that the monomer containing the silicate is any one of tetraethoxysilane, n-octyltriethoxysilane, siloxane and vinyltrimethoxysilane.
[0065] The monomer containing silicate acts as a cross-linking agent between silicon and graphene, and is used to consolidate the bonding force between silicon and graphene. At the same time, the remaining part except the part that acts as the cross-linking agent is removed during the spray drying or heat treatment process to realize a hollow structure inside, ensuring a gap so that the volume of silicon can easily expand during charging and discharging.
[0066] In addition, the present invention is characterized in that it also contains silicate.
[0067] Although not limited thereto, a salt such as lithium silicate may be included, the purpose of which is to remove the salt by preparing the solution again and filtering the process after spray drying, thereby achieving a hollow structure inside the silicon-graphene negative electrode material.
[0068] In addition, it is characterized in that the water-soluble polymer is selected from polyvinyl alcohol, polyethylene glycol, polyethyleneimine, polyamideamine, polyvinyl formamide, polyvinylacetate, polyacrylamide, polyvinylpyrrolidone, polydiallyldimethylammonium chloride, polyethyleneoxide, polyacrylic acid, polystyrenesulfonic acid, polysilicic acid, polyphosphoric acid, polyethylenesulfonic acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinyllacetate, poly-4-vinyllacetate, poly-4-vinyllacetate, poly-4-vinylphenylsulfuric acid ...lacetate, poly acid), Polyethyleneohosphoric acid, Polymaleic acid, Poly-4-vinylbenzoic acid, Methyl cellulose, Hydroxyethyl cellulose, Carboxymethyl cellulose, Sodiumcarboxymethyl cellulose, Hydroxypropylcellulose, Sodiumcarboxymethylcellulose, Polysaccharide, Starch and mixtures thereof.
[0069] Although not limited thereto, it is most preferable to use polyvinyl alcohol.
[0070] Afterwards, the composite powder preparation step (S 400 ).
[0071] A composite powder preparation step of spray-drying the composite dispersion solution prepared in the composite dispersion solution preparation step to prepare a composite powder in which silicon and graphene are formed into a core-shell structure may be performed.
[0072] According to one embodiment of the present invention, it is characterized in that the composite dispersion solution prepared in the composite dispersion solution preparation step is spray-dried at a temperature of 100 to 250°C.
[0073] When the spray drying temperature is lower than 100°C, i.e., when the temperature is too low, the spray drying cannot proceed normally and the residual liquid falls into the container. When the spray drying temperature exceeds 250°C and reaches an excessively high temperature, the pressure in the spray dryer may increase excessively, the oxidized or dried powder may boil, resulting in structural damage, increased energy consumption, and other problems.
[0074] Here, it is characterized in that the size of the composite powder prepared in the composite powder preparation step is 1 to 100 μm.
[0075] When the size of the composite powder is less than 1 μm, the amount of silicon used will be reduced, thereby reducing the capacity of the negative electrode material. When the size of the composite powder is greater than 100 μm, poor uniformity may occur when applied to the negative electrode substrate.
[0076] Although not limited thereto, the size of the composite powder prepared in the composite powder preparing step is most preferably 10 μm.
[0077] After the composite powder preparation step, a heat treatment step may be further included in which the composite powder prepared in the composite powder preparation step is heat treated at a temperature of 100 to 500° C. for 30 minutes to 4 hours in any one of air, nitrogen and argon atmospheres.
[0078] The purpose of the heat treatment step is to make graphene more firmly bonded to silicon and to smoothly form a hollow structure by removing water-soluble polymers. When the heat treatment temperature is too high, graphene oxide and reduced graphene oxide may be denatured or removed by thermal decomposition, and when the heat treatment temperature is too low, insufficient sintering may occur.
[0079] In addition, the present invention is characterized in that the core is composed of silicon metal particles and the shell is composed of graphene to form a silicon-graphene composite negative electrode material with a core-shell structure.
[0080] The graphene according to one embodiment of the present invention can be more clearly understood through the following examples. These examples are only used to help understand the present invention, and the scope of the present invention is not limited to these examples in any sense.
[0081] [Example 1]
[0082] Preparation of silicon-graphene composite negative electrode materials
[0083] 1. Preparation steps of graphene oxide:
[0084] 1) Oxidation step: 300 parts by weight of potassium permanganate, 15,000 parts by weight of water and 10,000 parts by weight of sulfuric acid were mixed with 100 parts by weight of expanded graphite and stirred, and reacted at 60° C. for 3 hours to prepare an oxidized graphite slurry.
[0085] 2) Filtration step: 100 parts by weight of water was mixed with 100 parts by weight of the prepared graphite oxide slurry, followed by centrifugal separation to discharge the filtrate and separate the graphite oxide slurry.
[0086] 3) Graphene oxide preparation step: 10000 parts by weight of water was mixed with 100 parts by weight of graphite oxide slurry, and the mixture was filtered after impurities were purified in an ion resin exchange tower to prepare a graphene oxide aqueous solution.
[0087] 2. Reduced graphene oxide preparation steps: freeze-drying the graphene oxide aqueous solution and then thermally reducing it to prepare reduced graphene oxide powder.
[0088] 3. Preparation of a composite dispersion solution: adding silicon metal particles and a cross-linking agent to a graphene oxide aqueous solution and reduced graphene oxide powder, stirring and dispersing the mixture to prepare a composite dispersion solution. The mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is added and dispersed in a ratio of 1 to 3 parts by weight relative to 100 parts by weight of the silicon metal particles, wherein the mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is mixed with the reduced graphene oxide powder in a ratio of not more than 200 parts by weight relative to 100 parts by weight of the graphene oxide aqueous solution.
[0089] Here, the lateral size of the graphene oxide and the reduced graphene oxide is 1 to 100 μm based on the median particle size (D50), the thickness is 0.6 to 10 nm, and the size of the silicon metal particles is 0.5 to 1 μm.
[0090] In addition, carbon black as a commercial carbon source may be further added here.
[0091] The crosslinking agent is a monomer containing silicate, and any one of tetraethoxysilane, n-octyltriethoxysilane, siloxane, and vinyltrimethoxysilane may be added. Silicate may be further contained.
[0092] In addition, polyvinyl alcohol was used as the water-soluble polymer.
[0093] 4. Composite powder preparation step: The composite dispersion solution is spray-dried at a temperature of 220°C to prepare a composite powder in which silicon and graphene form a core-shell structure. The core is a silicon metal particle and the shell is composed of graphene. The size of the prepared composite powder is 10 μm.
[0094] 5. Heat treatment step: The composite powder is heat treated at 200° C. for 1 hour in any one of air, nitrogen and argon atmospheres.
[0095] Four samples A, B, C and D were prepared in the above manner and used in Example 2 below.
[0096] [Example 2]
[0097] Quality characteristics of prepared silicon-graphene composite anode materials
[0098] 1. Confirm the initial capacity and stability of silicon-graphene composite anode materials
[0099] Table 1 shows the charge and discharge test results of the negative electrode material sample A prepared according to the present invention and the negative electrode material products of other companies. It is characterized in that the initial capacity of the silicon-graphene composite negative electrode material product prepared by the present invention is very high compared with the products of other companies, because graphene is used to improve the inherent properties of silicon. The products of other companies only show performance corresponding to the silicon content because a large amount of carbon source and silicon dioxide are mixed in silicon, so the performance is lower than the negative electrode material of the present invention. However, the capacity retention rate of the negative electrode material of the present invention is relatively lower than that of other products, and it is judged that this is caused by the cracking phenomenon of silicon.
[0100]
Table 1
[0101]
[0102] 2. Silicon-graphene composite state
[0103] Down Figure 2 : is a photograph showing the state of the silicon-graphene composite. The state of the silicon-graphene composite was confirmed with sample A as the object, see below Figure 2 It can be confirmed that the graphene effectively wraps the silicon clusters well.
[0104] 3. Comparison of silicon-graphene composite negative electrode material composition
[0105] Table 2 below compares the composition of graphite and negative electrode materials of silicon-graphene composite negative electrode materials and the solid content relative to the target capacity. The target capacity is set to 450mAh / g, and the solid content is preferably 50% to 60%. Products of other companies, including the negative electrode material of the present invention, all show a solid content of more than 50%.
[0106]
Table 2
[0107]
[0108] 4. Charge and discharge test of silicon-graphene composite negative electrode material
[0109] Down Figure 4 It is a graph showing the charge and discharge test results of the silicon-graphene composite negative electrode material. The X-axis represents the charge amount, the Y-axis represents the discharge amount, the L-shaped curve represents the charge curve, and the inverted L-shaped curve represents the discharge curve. It can be confirmed from the charge and discharge test results of the negative electrode material that the discharge amount is less than the charge amount.
[0110] 5. Cycling characteristics of silicon-graphene composite anode materials
[0111] Figure 5 below is a graph of the cycle characteristics of the silicon-graphene composite negative electrode material. It can be used to determine the capacity retention rate. The discharge capacity does not decrease significantly until 100 cycles, and the discharge capacity can be maintained at about 400mAh / g.
[0112] The present invention is described in detail above through the embodiments, but the present invention is not limited to the above embodiments and can be modified in various ways. It is obvious that a person skilled in the art can make various modifications within the technical concept of the present invention. In addition, a person skilled in the art can make various substitutions, modifications and changes within the scope of the technical concept of the present invention as described in the claims, which also belong to the scope of the present invention.
Claims
1. A method for preparing a silicon-graphene composite negative electrode material, characterized in that: include: A graphene oxide preparation step of preparing a graphene oxide aqueous solution by a modified Hummers method; A reduced graphene oxide preparation step of freeze-drying the graphene oxide aqueous solution prepared in the graphene oxide preparation step and then thermally reducing it to prepare reduced graphene oxide powder; a composite dispersed solution preparation step of adding silicon metal particles, a crosslinking agent, and a water-soluble polymer to the graphene oxide aqueous solution prepared in the graphene oxide preparation step and the reduced graphene oxide powder prepared in the reduced graphene oxide preparation step, followed by stirring and dispersing to prepare a composite dispersed solution; as well as A composite powder preparation step is to spray-dry the composite dispersion solution prepared in the composite dispersion solution preparation step to prepare a composite powder in which silicon and graphene are formed into a core-shell structure.
2. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: In the graphene oxide preparation step, a graphene oxide aqueous solution is prepared by an improved Hummers method, and the improved Hummers method comprises an oxidation step of preparing a graphite oxide slurry by mixing expanded graphite, potassium permanganate, water and sulfuric acid and stirring and maintaining a predetermined temperature to react for a predetermined time, a filtering step of mixing 50 to 200 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry prepared in the oxidation step, and then centrifuging to discharge the filtrate and separate the graphite oxide slurry, and a graphene oxide preparation step of preparing a graphene oxide aqueous solution by mixing 5000 to 20000 parts by weight of water with respect to 100 parts by weight of the graphite oxide slurry separated in the filtering step, purifying impurities in an ion resin exchange tower, and filtering.
3. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The lateral size of the graphene oxide and the reduced graphene oxide is 1 to 100 μm based on the median particle size D50, and the thickness is 0.6 to 10 nm.
4. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: In the composite dispersion solution preparation step, The mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is added and dispersed in a ratio of 1 to 3 parts by weight relative to 100 parts by weight of the silicon metal particles.
5. The method for preparing a silicon-graphene composite negative electrode material according to claim 2, characterized in that: The mixture of the graphene oxide aqueous solution and the reduced graphene oxide powder is mixed with the reduced graphene oxide powder in a ratio of within 200 parts by weight relative to 100 parts by weight of the graphene oxide aqueous solution.
6. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The size of the silicon metal particles is 0.05 to 5 μm.
7. The method for preparing a silicon-graphene composite negative electrode material according to claim 6, characterized in that: The size of the silicon metal particles is 0.5 to 1 μm.
8. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: In the composite dispersion solution preparation step, a commercial carbon source consisting of any one or more of natural graphite, artificial graphite, carbon black, acetylene black, graphite intercalated compound (GIC), expanded graphite, activated carbon, graphene nanoplatelets (GNP) and carbon nanotubes (CNT) is added and dispersed and mixed.
9. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The crosslinking agent is composed of monomers containing silicate esters.
10. The method for preparing a silicon-graphene composite negative electrode material according to claim 8, characterized in that: The monomer including the silicate is any one of tetraethoxysilane, n-octyltriethoxysilane, siloxane, and vinyltrimethoxysilane.
11. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The composite dispersion solution preparation step further includes silicate.
12. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The water-soluble polymer is selected from the group consisting of polyvinyl alcohol, polyethylene glycol, polyethyleneimine, polyamideamine, polyvinyl formamide, polyvinyl acetate, polyacrylamide, polyvinylpyrrolidone, polydiallyldimethylammonium chloride, polyethyleneoxide, polyacrylic acid, polystyrenesulfonic acid, polysilicic acid, polyphosphoric acid, polyethylenesulfonic acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinylphenol, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-4-vinylphenylsulfuric acid, poly-3-vinyloxypropane-1-sulfonic acid, poly-4-vinyl acid), Polyethylene ohosphoric acid, Polymaleic acid, Poly-4-vinylbenzoic acid, Methyl cellulose, Hydroxy ethyl cellulose, Carboxy methyl cellulose, Sodium carboxy methyl cellulose, Hydroxy propylcellulose, Sodium carboxymethyl cellulose, Polysaccharide, Starch, and any one or more of a mixture thereof.
13. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: In the composite powder preparation step, the composite dispersion solution prepared in the composite dispersion solution preparation step is spray-dried at a temperature of 100 to 250°C.
14. The method for preparing a silicon-graphene composite negative electrode material according to claim 1, characterized in that: The size of the composite powder prepared in the composite powder preparation step is 1-100 μm.
15. The method for preparing a silicon-graphene composite negative electrode material according to any one of claims 1 to 14, characterized in that: After the composite powder preparation step, the method further comprises: A heat treatment step of heat-treating the composite powder prepared in the composite powder preparation step at a temperature of 100 to 500° C. for 30 minutes to 4 hours under any one of an atmosphere gas of air, nitrogen and argon.
16. A silicon-graphene composite negative electrode material, characterized in that: The core is composed of silicon metal particles and the shell is composed of graphene to form a core-shell structure.
17. A silicon-graphene composite negative electrode material, characterized in that: It is prepared by the preparation method according to claim 15 and formed into a core-shell structure.
Citation Information
Patent Citations
Method for manufacturing silicon-graphene based complex composite in use of anode material for secondary battery
KR101399042B1